Analisis Pemanfaatan Rainwater Harvesting untuk Pemenuhan Kebutuhan Air Non-domestik - Muhammad Zahran Fakhri; Rizal Arif Setiawan; Henny Pratiwi Adi (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
The increasing demand for clean water at the Faculty of Engineering, Sultan Agung Islamic University (UNISSULA) Semarang requires an alternative and sustainable water source. One effective solution is the implementation of a rainwater harvesting (RWH) system to meet non-domestic water needs such as toilet flushing, plant irrigation, and campus cleaning. This study aims to analyze the potential utilization of rainwater, design an appropriate RWH system, and evaluate its cost efficiency compared to the use of PDAM (regional water supply company) water. This research employed a quantitative approach by collecting primary data, including roof catchment area measurements and existing rainwater drainage conditions, as well as secondary data such as average rainfall, the number of campus users, and PDAM water tariffs. The analysis consisted of calculating the potential harvested rainwater volume, designing the RWH system, estimating installation costs, and comparing operational costs between RWH and PDAM water usage. The results indicate that the potential harvested rainwater volume from the building’s roof is approximately 7,054.5 liters/day, while the average non-domestic water demand is 3,170 liters/day, allowing water needs to be met during the rainy season. The implementation of the RWH system can also reduce water costs by up to 43,6%, equivalent to IDR 87.615.616 over a 20-year period. Therefore, the application of RWH is an effective and sustainable solution for water management within the campus while supporting operational cost efficiency.